Mutações no papel dos jornais : estudo de caso da imprensa capixaba - Caldas, Weber Kirmse (2018)
This work deals with the changes undergone by the newspapers in their process of convergence for the new digital media. The research studies the strategies adopted by companies in the migration of print media from paper to the internet, at a time of crisis of this business model. It seeks to understand how this media can survive and escape the death announced by threats brought by the "age of hyperinformation" and the Network Society (CASTELLS, 2001), such as the fall in circulation, the reduction of revenues the saturated market of journalism and the competition of new media. What new newspaper is emerging from the ongoing mutations? In the search for this answer, the theoretical precepts of the Cultural Industry and the Political Economy of Communication are used, as well as a historical recovery from the appearance to the evolution of the printed media. And the newspapers A Gazeta and A Tribuna and their respective sites are used as a source of investigation, through a content analysis based on two case studies.